THE EFFECTIVENESS OF ENGLISH SONGS IN TEACHING VOCABULARY TO THE SIXTH GRADE PUPILS - Ferina Rizkiani (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2022)
This research was held at SDN Sungai Bambu 05 Pagi. The objective of the study is to find the empirical evidence of whether or not English songs are effective in teaching vocabulary to the sixth grade pupils. The samples of this study were 28 students of VI D. The writer used quantitative design by employing pre-experiment method in taking this research. She used vocabulary test to find the students vocabulary pre-test and post-test scores and use t-test to analyse the effectiveness of English songs in the teaching of vocabulary. The test consisted of two parts; multiple choice, and matching with the total 50 items. After describing and analysing the data, it can be concluded that English songs are effective as an alternative strategy in the teaching vocabulary to the sixth grade pupils. It is proven that there is a significance score after several treatments in the classroom. Moreover, the benefits of the research result are the teacher and the students feel more relaxed, less-stressful, and happy, the teacher and the students gain new word from the lyric so, they will try to pronounce the words, and the teacher and the students become more active.